PENGEMBANGAN SUMBER DAYA APARATUR DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALU PROVINSI SULAWESI TENGAH - Setiyaningsih, Roro (Katalogis, 2017)
The purpose of this study was to determine the development of apparatus resources at Palu City Department of Population and Civil Registration. Types of data used were primary and secondary data. Data collection techniques in this study were observations, interviews, and documentations. Informants of this study amounted to 7 (seven) people. This study used the data analysis model of Miles and Huberman, namely data reduction, data presentation, and conclusion. The theory used was the theory of Armstrong. The apparatus resources development at Palu City Department of Population and Civil Registration was still less good. It could be known from the four aspects, namely Learning aspect where the employees lacked learnings related to the tasks, Training aspect where the employees lacked trainings in performing the tasks, Development aspect where the placement of employees lacked compatibilities between education and office held, and Education aspect where there were still many employees who were lacking in higher level education.